2011
DOI: 10.1111/j.1756-5391.2011.01123.x
|View full text |Cite
|
Sign up to set email alerts
|

Patient Safety Research in China: A Literature Review

Abstract: Objective A number of articles on patient safety have been published in Chinese‐language journals in last decade. However, until now there have been no studies of their overall quality or contribution to current thinking. This study explored the themes and designs of studies on patient safety published in Chinese‐language journals. Method We searched the major Chinese databases, Chinese Biomedical Literature Database (CBM) and Chinese Journals Full‐text Database (CNKI), for Chinese‐language patient safety res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…Comparative studies and systematic reviews that are considered of better quality in design were very rare in all the included articles. Our findings were similar to those in other patient safety study . More rigorously designed methodologies have been generally encouraged in patient safety research in recent days by WHO Patient Safety Program addressing that it is based on the principle that effective improvement requires sound local evidence about the nature and extent of existing problems and risks including producing high‐quality patient safety research by selecting and implementing the most appropriate methods.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Comparative studies and systematic reviews that are considered of better quality in design were very rare in all the included articles. Our findings were similar to those in other patient safety study . More rigorously designed methodologies have been generally encouraged in patient safety research in recent days by WHO Patient Safety Program addressing that it is based on the principle that effective improvement requires sound local evidence about the nature and extent of existing problems and risks including producing high‐quality patient safety research by selecting and implementing the most appropriate methods.…”
Section: Discussionsupporting
confidence: 87%
“…To date, many countries have initiated patient safety culture research, especially in developed countries . On a global basis, several international organizations have significantly contributed to the promotion of the culture of patient safety, such as the World Alliance for Patient Safety, the National Patient Safety Agency in the UK, and the Agency for Healthcare Research and Quality in USA, etc . Our recent initial literature searching on patient safety including Chinese Biomedical Literature Database and Chinese Journals Full‐text Database has also yielded a total of 40,375 relevant studies .…”
Section: Introductionmentioning
confidence: 99%
“…In Mainland China, a focus on patient safety occurred no earlier than 2007. 13 Moreover, while there have been many influential studies on patient safety in developed countries, such as those mentioned above, a review of Chinese patient safety studies 14 concluded that the overall quality of those studies needs improvement, especially in terms of methodological rigor.…”
Section: Introductionmentioning
confidence: 99%
“…Many staff with insufficient experience and inadequate attention to patient safety represent a risk to patients and other nurses [69]. Nurses play a central role in improving the patient safety culture [18] and addressing patient safety issues [70] as they monitor patients' clinical conditions, detect errors, and understand care processes and system weaknesses to provide high-quality care [17]. In work environments with a patient safety-focused program, the leadership can positively influence the effectiveness of employees' work, their awareness, and their involvement in improving the quality and safety of care [71].…”
Section: Discussionmentioning
confidence: 99%